2013
DOI: 10.1177/1089253213514484
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management Strategies for Thoracotomy and Thoracic Pain Syndromes

Abstract: Pain after thoracic surgery can be severe and, in the acute phase, contribute to perioperative morbidity and mortality. Unfortunately, patients also incur a significant risk of chronic pain. Although there are guidelines for postoperative pain management in these patients, there is no widespread surgical or anesthetic "best practice." Here, we review the recent literature on techniques specific to perioperative pain control for thoracic patients, including medical management, neuraxial blockade, and other regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 92 publications
(98 reference statements)
0
36
0
Order By: Relevance
“…This complex is also known as postthoracotomy pain syndrome (PTPS) (17). The reported incidence is quite high, ranging from 30% to 80% by varied studies but without difference between VATS and thoracotomy (3,18). In this study we questionnaire the patients by telephone three months after procedure and found that parecoxib significantly reduced the incision related pain.…”
Section: Discussionmentioning
confidence: 64%
“…This complex is also known as postthoracotomy pain syndrome (PTPS) (17). The reported incidence is quite high, ranging from 30% to 80% by varied studies but without difference between VATS and thoracotomy (3,18). In this study we questionnaire the patients by telephone three months after procedure and found that parecoxib significantly reduced the incision related pain.…”
Section: Discussionmentioning
confidence: 64%
“…Several strategies have been introduced for POP management [35] . It is believed that multimodal analgesic approaches combining different analgesic agents with different mechanisms of action can maximize pain relief while minimize the opioid consumption and thus can limit the opioid-induced side effects [6,36] .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that multimodal analgesic approaches combining different analgesic agents with different mechanisms of action can maximize pain relief while minimize the opioid consumption and thus can limit the opioid-induced side effects [6,36] . As a method of limiting opioid-induced adverse events, therefore, multimodal POP management has the potential to decrease morbidity and mortality after surgery [35] . Consequently, it is expected that the sedative, anesthetic, analgesic, and cardiorespiratory effects of DEX may enhance with concomitant administration with other anesthetic, sedative and analgesic medications [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no single drug or drug combination is completely effective in all patients . Moreover, side effects are common with prolonged use of these drugs, and tolerance can develop after opioid use . Preemptive analgesia was also not effective in reducing chronic postthoracotomy pain …”
Section: Discussionmentioning
confidence: 99%